Quetiapine safety in older adults: a systematic literature review. (February 2016) - El‐Saifi, N.; Moyle, W.; Jones, C.; Tuffaha, H.
Summary: What is known and objective: Quetiapine is a second‐generation antipsychotic that is commonly prescribed for a range of approved and off‐label indications in older adults. However, little is known about its safety in this population. The available evidence on quetiapine safety is based on studies on second‐generation antipsychotics as a group, often in the general population and for approved indications. There are no systematic reviews on the safety of quetiapine in older adults, and therefore, there is a need for systematically assessing quetiapine safety in this group of patients to establish an appropriate safety profile for this vulnerable population. The aim of this paper was to review and describe adverse drug events associated with quetiapine use in older adults. Methods: A systematic literature search was performed based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Databases searched were CINAHL, PubMed, Medline, PsycInfo and the Cochrane Library. Results and discussion: Sixty‐nine papers met the inclusion criteria. The majority of the studies ( n = 36, 52%) were observational, and 11 (16%) were randomized controlled trials (RCTs). Most of the reported indications (75%) were off‐label. The most commonly reported adverse events were somnolence (25–39%), dizziness (15–27%), headache (10–23%), postural hypotension (6–18%) and weight gain (11–30%). From the included RCTs, comparing quetiapine with placebo, quetiapine resulted in significantly greater cognitive impairment, higher rates of falls and injury and increased mortality in patients with parkinsonism, but not in patients with dementia. Compared with risperidone and olanzapine, quetiapine had significantly lower risk of mortality, reduced rate of cerebrovascular events, increased rate of falls and injury and less metabolic disorders compared with olanzapine, but higher metabolic disorders compared with risperidone. What is new and conclusion: This work provides full characterization of quetiapine safety in older people, which may help healthcare providers better anticipate, prevent and manage ADEs in this population. Abstract : This is a systematic literature review of quetiapine safety in older people. It provides full characterization of quetiapine adverse drug events in terms of type, frequency and outcomes, which will help healthcare providers better manage unwanted quetiapine events in this population.